Ideological Violence and Reprisals at Kaunas State Vytautas Magnus University (1944–1950) - Veilentienė, Audronė (Genocidas ir rezistencija, 2013)
At the end of WWII, when the second Soviet occupation of Lithuania started, it was accompanied by Sovietisation, terror, and ideological-moral coercion carried out by the USS R. The same methods were applied to institutions of higher education. Professors and students of Kaunas State Vytautas Magnus University were arrested, deported, expelled from the university, and forced to study pseudo-scientific disciplines, participate in Soviet festivities, during lectures glorify Russian and Soviet scientists and their achievements, and derogate the history, culture and science of Lithuania. The occupation authorities tried to “re-educate” the national intelligentsia formed during the time of independent Lithuania and to train loyal intellectuals. Therefore, individuals who did not suit the Soviet government were removed from the university by admitting mostly the children of workers and peasants to the university. Repression and ideological coercion at the university were organised and carried out by members of the Communist Party and Komsomol. These measures, however, failed to destroy the spirit of the national university, and as a result the USR Ministry of Higher Education reorganised the university, renaming it Kaunas Polytechnic Institute (today Kaunas University of Technology). The ministry renamed the Faculty of Medicine of the university Kaunas Medical Institute (today Lithuanian University of Health Sciences).
Keywords: soviet occupation; high education; ideological indoctrination; repressions